2008
DOI: 10.1007/s10694-008-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

The Use of CFD Calculations to Evaluate Fire-Fighting Tactics in a Possible Backdraft Situation

Abstract: This paper is an attempt to integrate theoretical Computational Fluid Dynamics (CFD) calculations with practical fire-fighting tactics commonly used when arriving at the scene of an underventilated fire. The paper shows that CFD has a great potential in improving understanding and creating better effectiveness in the estimation of fire-fighting tactics. If burning has occurred in a lack of oxygen for a long time, excessive pyrolysis products may have accumulated in the fire compartment. If air is suddenly intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…4, only the inside flow is seeded and it shows the formation of a small-scale pair of counter-rotating vortices (Obs 4.1) between cold entering air and hot inside air. The time resolved sequences of images shows successive vortex coalescence process where pairs of Van Karman vortices are ingested into a single large vortex [8]. Other visualizations have shown pulsating disturbances at the opening despite minimizing air disturbance in the room.…”
Section: Quantitative Results -Visualization With Fast Tomographymentioning
confidence: 94%
See 1 more Smart Citation
“…4, only the inside flow is seeded and it shows the formation of a small-scale pair of counter-rotating vortices (Obs 4.1) between cold entering air and hot inside air. The time resolved sequences of images shows successive vortex coalescence process where pairs of Van Karman vortices are ingested into a single large vortex [8]. Other visualizations have shown pulsating disturbances at the opening despite minimizing air disturbance in the room.…”
Section: Quantitative Results -Visualization With Fast Tomographymentioning
confidence: 94%
“…If an opening occurs, for example a window breaks or firefighters open a door to the room, fresh oxygen is carried into it by gravity currents, and mixes with these gases. The mixing of gas with oxygen can create a flammable mixture resulting in ignition and an explosive or rapid combustion called backdraft [6][7][8][9][10]. The deflagration propagates, causing an extreme pressure build-up [11].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, it has been investigated if the alternative spelling affects the total number of unique articles found, and that is not the case The firefighter as regulator Fire and Explosions Conf. paper [36] The Use of CFD Calculations to Evaluate FireFighting Tactics in a Possible Backdraft Situation Fire Technology Peer reviewed journal [37] Sensor Assisted Fire Fighting Fire Technology Peer reviewed journal [38] Improvement of Positive Pressure Ventilation by optimizing stairwell door opening area Fire Safety Journal Peer reviewed journal [39] 88 Fire Technology 2019 ignored at this stage was, as in the previous stage, not related to fire service activities. Furthermore, publications older than 20 years were not included because the intention of this work is to give a view of the current situation.…”
Section: Screen and Selection Of Publications Based On Entire Publicationmentioning
confidence: 99%
“…By using methane as the fuel source of fire in the experimental domain, Weng and Fan [25] found a critical mass fraction of unburned gases of 9.8%. Guigay et al [26] carried out an experiment on the possible actions being able to prevent the occurring of backdraft that showed that the cooling of gases in the enclosure on fire would reduce the difference in density between hot gases and cooled gases. is would therefore decrease the effects of the relaxation of hot gases in the event of an abrupt contribution of fresh air.…”
Section: Introductionmentioning
confidence: 99%